Genotype differences in gonadal and extragonadal sperm reserves in mature Zebu bulls in Ethiopia - Tegegne, Azage; Mukasa-Mugerwa, E.; Entwistle, K.W. (Elsevier, 1992)
Gondal and extragonadal sperm reserves were determined in testicular and epididymal tissues obtained from ten Small East African Zebu (SEAZ), ten unimproved Borana and nine improved Boran bulls. Bulls were mature and were between 6 and 8 years of age. Body weight and scrotal circumference differed significantly among the three genotypes. Body weight was 281, 329 and 524 kg. for SEAZ, Borana and Boran bulls respectively and scrotal circumference 28.7, 30.9 and 36.4 cm. Paired testes and epididymal weights averaged 322, 359 and 582 g and 36.7, 40.9 and 64.6 g for SEAZ, Borana and Boran bulls, respectively and were significantly larger in Boran bulls than in the other two geneotypes. Daily sperm production (DSP) did not differ between the three genotypes. However, Boran bulls had significantly larger DSP than the other two. Epididymal sperm reserves differed significantly between the three genotypes with SEAZ having the least followed by Borana and Boran.